Islamic macroeconomics a model for efficient government, stability and full employment - Almarzoqi, Raja; Mansour, Walid; Krichene, Noureddine (Islamic business and finance series, 2018)
Islamic Macroeconomics proposes an Islamic model that offers significant prospects for economic growth and durable macroeconomic stability, and which is immune to the defects of the economic models prevailing both in developed and developing countries. An Islamic model advocates a limited government confined to its natural duties of defence, justice, education, health, infrastructure, regulation, and welfare of the vulnerable population.